2021
DOI: 10.1002/ange.202105231
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Alkaline Stability of N‐Heterocyclic Ammonium Groups for Anion‐Exchange Polyelectrolytes

Abstract: The alkaline stability of N‐heterocyclic ammonium (NHA) groups is a critical topic in anion‐exchange membranes (AEMs) and AEM fuel cells (AEMFCs). Here, we report a systematic study on the alkaline stability of 24 representative NHA groups at different hydration numbers (λ) at 80 °C. The results elucidate that γ‐substituted NHAs containing electron‐donating groups display superior alkaline stability, while electron‐withdrawing substituents are detrimental to durable NHAs. Density‐functional‐theory calculations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…[17][18][19] (ii) Years of study have revealed that most cationic groups (such as ammonium and phosphonium) and aryl ether polymer backbones are vulnerable and likely to degrade under alkaline conditions. [20][21][22][23] (iii) High IEC AEMs are needed to improve the ion conductivity of AEMs. However, the mechanical properties and dimensional stability of AEMs are inevitably sacriced upon an increase of IEC due to excessive water uptake and the swelling ratio.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] (ii) Years of study have revealed that most cationic groups (such as ammonium and phosphonium) and aryl ether polymer backbones are vulnerable and likely to degrade under alkaline conditions. [20][21][22][23] (iii) High IEC AEMs are needed to improve the ion conductivity of AEMs. However, the mechanical properties and dimensional stability of AEMs are inevitably sacriced upon an increase of IEC due to excessive water uptake and the swelling ratio.…”
Section: Introductionmentioning
confidence: 99%
“…The alkaline stability of the composite membrane was studied in 30 wt% KOH at 80 °C (Fig. 3h), with the all-in-one MEA-S showing a negligible change in area resistance after alkaline treatment for 1000 h. As expected, the excellent chemical stability of the composite membrane in the all-in-one MEA-S resulted from the ether-free polymer backbone and chemically stable metal sulfide 32,33 . However, the commercial Zirfon Thin, m-PBI and Sustainion X37-50 membranes exhibited 18%, 30% and 45% increases in area resistance after durability testing for 1000 h. Furthermore, the change in the mechanical properties of the membranes after alkaline stability testing was investigated.…”
Section: Resultsmentioning
confidence: 52%
“…For instance, strategies for polymer functionalization, polycondensation (Noh et al, 2019) or cationic structures design (Tao et al, 2021) require a highly stable membrane; nevertheless, their long-term stability in practical operating conditions has not yet been verified. Although there has been progress in developing innovative polymer materials with high stability [such as poly (aryl piperidinium)based and poly (arylene piperidine)-based anion exchange membranes (Chen et al, 2021;Pan et al, 2021)], transformative alternative membranes as efficient as Nafion for energy storage and conversion devices are urgently needed. Another scientific challenge remains to be addressed, i.e., obtaining an ion exchange membrane that can satisfy the need for energy storage and conversion devices, including high ionic conductivity, outstanding selectivity, ease of processability, and high environmental sustainability.…”
Section: Challenges For Ion Exchange Membranementioning
confidence: 99%